Development of Biscuits Made from Maggot Flour and Whey Protein Isolate as a High-Protein Snack for School-Age Children - Prita Dhyani Swamilaksita; Fajria Arnesya Maharani; Reza Fadhilla (PT FORMOSA CENDEKIA GLOBAL, 2023)
Intake of nutrients has an important role in the growth and development of school-age children; one of them is protein. A sufficient protein intake can support brain development and intelligence so that they can learn well. In general, making biscuits using only wheat flour, which only contains macronutrients and contains few other nutrients, Through the addition of maggot flour and whey protein isolate, it is expected to increase the nutritional value of biscuits, especially protein. The method used in this study was experimental. The organoleptic test using the VAS (Visual Analog Scale) method was performed by 25 semi-trained panelists. The results showed that the addition of different maggot flour and whey protein isolates had a significant effect (p≤0,05) on the quality and content of the biscuits. Treatment with the addition of 70 gr maggot flour and 50 gr whey protein isolate resulted in the highest protein value of 19,28%. While the results of the acceptance test of biscuits treated with the addition of 50 gr maggot flour and 70 gr whey protein isolate were the most preferred biscuits overall, The more maggot flour added to the biscuit dough, the higher the protein value.